Art therapy nusantara: Integrating local arts to strengthen self-esteem and mental health - Anisa Yulia Kurniawati; Fendi Krisna Rusdiana (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia's rich cultural heritage provides a foundation for integrating traditional arts into psychological interventions. Art therapy has long been recognized for its significant potential in enhancing emotional regulation and self-esteem. However, most existing interventions are rooted in a Western context, thus neglecting local cultural values. This study aims to explore the application of art therapy based on local Indonesian culture as a means to enhance self-esteem and emotional well-being. Methods: This study employed a qualitative approach based on literature studies by analyzing various empirical findings related to art therapy, self-esteem, and cultural adaptation in mental health interventions. The analysis focused on identifying cultural elements that can be integrated into art therapy, such as batik-making, gamelan-playing, and pantun-writing, and examining the psychological mechanisms underlying their therapeutic impact. Findings: The study showed that the creative process in traditional arts not only serves as a means of emotional release but also encourages self-reflection, identity formation, and cultural pride. Activities such as batik-making and gamelan-playing collectively foster patience, concentration, and togetherness, which play a role in strengthening self-esteem. Furthermore, recent research, conducted in 2023–2024, demonstrated that structured art therapy can enhance multidimensional self-esteem. However, challenges such as limited facilitator competency, the risk of reducing cultural meaning, and limited access remain major obstacles to the implementation of culture-based art therapy in Indonesia. Conclusion: Integrating local arts into therapeutic practice is a promising and contextual approach to improving the mental health of Indonesians. This study emphasizes the importance of collaboration between mental health professionals and arts and culture practitioners to ensure that arts-based interventions maintain psychological integrity and cultural values. Novelty/Originality of this article: This study contributes to the development of culture-based psychology by proposing a conceptual model of art therapy unique to Indonesia. This model emphasizes the synergy of modern psychotherapy approaches with traditional arts wisdom as a sustainable and culturally relevant intervention to improve self-esteem and mental well-being.